Gender Hegemony in Denis Villeneuve’s Blade Runner 2049 (2017) - Rahadian Nugraha; Safrina Noorman (Universitas Pendidikan Indonesia (UPI), 2021)
The issues regarding gender hegemony in literary works have been widely discussed; yet only few relate the issue to non-human characters. Non-human characters, in this case, are characters which are technologically made and thought-driven being with a lesser capacity for emotion. This study was conducted to investigate how gender hegemony for non-human characters is constructed in a film. The non-human characters that were analyzed are K and Joi from Blade Runner 2049 (2017), a science fiction film directed by Denis Villeneuve. K is portrayed as a male synthetic being called the replicant, while Joi is portrayed as a female holographic digital companion called a DiJi. To investigate gender hegemony among the characters, this study applied Schipper’s (2007) framework of gender hegemony, Boggs and Petrie’s (2008) theory of characterization, and Heintz and Stracey’s (2006) film elements to analyze the hierarchy of masculinity and femininity in the film. The analysis revealed that the gender hegemony in the film is constructed through the exploitation of characterization, particularly between K and Joi who are presented with stereotypical hierarchical gender characteristics. These stereotypical characteristics created a gendered hegemony revolving around three major themes, namely love, loyalty, and revenge. Further exploration implies that, because the gender hegemony is very embedded in the film, the filmmaker could not offer an alternative of male-female relationships for non-human characters. Keywords: Blade Runner, femininity, gender hegemony, masculinity, non-human characters